Risks of leukapheresis and how to manage them: a non-systematic review - Stenzinger, Miriam; Bönig, Halvard (Transfusion and apheresis science, 2018)
Abstract: Leukapheresis is like any other preparative apheresis, except it isn't: Leukapheresis typically takes much longer, larger blood volumes are processed and, consequently, larger ACD-A volumes are administered. Blood component donors and leukapheresis subjects are also quite different populations. Allogeneic donors tend to be younger and many are first-time donors, both of which are risk factors for adverse reactions during blood donation. Moreover, more than half of all leukapheresis collections are performed in patients. Here it is the age distribution, including patients at the extremes of age, as well as the underlying disease and co-morbidities which may expose them to higher, or different, risks compared to donors. Both groups thus have good reasons why adverse effects to leukapheresis might be more frequent, more severe, or even different in nature altogether. Compared to other preparative apheresis types like platelet or plasma apheresis, the risks of leukapheresis have been studied less extensively, as it is in comparison a relatively low-frequency intervention. Often leukapheresis remains a domain of hematologists who have a different sense of procedural safety than transfusionists. Furthermore, G-CSF mobilized "stem cell" aphereses by a wide margin outnumber unmobilized aphereses, so that the very strong signal from adverse reactions to G-CSF all but drowns out signals from the apheresis proper. This focused review assesses observations from leukapheresis as well as extrapolation of observations from other forms of preparative apheresis in an attempt to gauge the safety of leukapheresis and identify potential approaches to its further improvement. In short, the overall impression is one of a very satisfactory safety record of leukapheresis, with occasional issues with venous access or vasovagal problems, and frequent, but highly responsive and rarely limiting ACD-A toxicity.